An intersection test for the cointegrating rank in dependent panel data - Antonia Arsova; Deniz Dilan Karaman Örsal (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2016)
This paper takes a multiple testing perspective on the problem of determining the cointegrating rank in macroeconometric panel data with cross-sectional dependence. The testing procedure for a common rank among the panel units is based on Simes' (1986) intersection test and requires only the p-values of suitable individual test statistics. A Monte Carlo study demonstrates that this simple test is robust to crosssectional dependence and has reasonable size and power properties. A multivariate version of Kendall's tau is used to test an important assumption underlying Simes' procedure for dependent statistics. The method is illustrated by testing the validity of the monetary exchange rate model for 8 OECD countries in the post-Bretton Woods era.
Keywords: C12; C15; C33; 330; panel cointegration rank test; cross-sectional dependence; multiple testing; common factors; likelihood-ratio